P-185 Microbial-Dependent CX3CR1+ MNP Production of TL1A Co-stimulates ILC3 to Promote Mucosal Healing. (March 2016) - Castellanos, Jim; Victorio, Daniel; Abdulhamid, Ahmed; Kivolowitz, Charles; Diehl, Gretchen; Shih, David; Scherl, Ellen; Longman, Randy
Abstract : Background: Colonic lamina propria mononuclear phagocytes (MNPs) expressing the fractalkine receptor CX3 CR1 play a critical role in maintaining barrier homeostasis. Recently, we have shown that these MNPs promote mucosal healing in response to microbial signals by supporting group 3 innate lymphoid cell (ILC3) production of IL-22 in both mouse models and human colitis. Mechanistically, we identified a role for CX3 CR1+ MNP production of TNF family cytokine TL1A—whose gene, TNFSF15, encodes functional polymorphisms strongly associated with IBD—in regulating ILC3 effector cytokine production; however, the mechanism and physiologic importance of TL1A expression by MNPs and signaling via receptor DR3 in promoting mucosal healing have not been defined. Methods: CX3CR1-GFP mice were used to evaluate TL1A expression in intestinal MNPs. Gnotobiotic mice and human endoscopic biopsy specimens were used to evaluate the role for microbiota and colitis, respectively, in driving TL1A expression. To examine the physiologic role for DR3 in mucosal healing, mice deficient for DR3 and littermate controls were exposed to 2% dextran sodium sulfate (DSS) for 7 days. Lamina propria mononuclear cells were analyzed ex vivo to evaluate effector cytokine production by ILC3 and to characterize the responsible signaling pathway. Results: Analysis of MNPs ex vivo revealed reduced TL1A expression in germ free mice compared to SPF controls, and colonization with segmented filamentous bacteria was sufficient to induce TL1A expression by qPCR. Consistent with the microbial-dependence of TL1A production, CD11c+ MHCII+ CX3 CR1+ splenocytes were upregulated TL1A in response to LPS stimulation in vitro. During DSS-induced colitis, increased expression of surface TL1A was seen in MHCII+ CX3 CR1+ LPMCs. An increase in TL1A expression was similarly seen in CD14 + MHCII + LPMCs from IBD patients. In response to DSS challenge, DR3-deficient mice had significantly more weight loss, more severe pathology, and reduced survival. Analysis of lamina propria cellular immune responses revealed a statistically significant reduction in innate lymphoid cell (Lin − /CD127 + ) production of IL-22 and GM-CSF. No difference in Th1, Th17, Treg, Foxp3/RORgt + CD4 + T, or ILC2 production of IL-13 was seen, suggesting a critical role for DR3 signaling in ILC3 in vivo . Our data in ILC3 show that TL1A synergy with IL-23 is independent of IL-1R and MyD88 signaling and not complemented by related TNFSF members (including OX40L, TRAIL, or TNFa). Soluble inhibitors revealed a critical role for MAPK signaling—specifically p38 MAPK—in mediating DR3 co-stimulation of ILC3. Conclusions: Collectively, these data highlight a key role for microbial regulation of MNP-derived TL1A in co-stimulating ILC3 effector cytokine production in vivo via p38 MAPK signaling. A mechanistic understanding of both the microbial components which induce TL1A in MNPs and the critical signaling pathways required for ILC3 co-stimulation will provide therapeutic targets to promote mucosal healing.